Una perspectiva curricular del enfoque de los sistemas simbólicos en la educación costarricense - Delgado Montoya, William (2012)
This article proposes an approach to education from the perspective of the theory of multiple and emotional intelligences. Intelligence is understood as the capacity to solve problems or create valuable products for a certain community or culture. Therefore, success or failure at school could be predicted based on the child’s capacity to solve problems and adapt to different social or natural sceneries. From this perspective, education is seen as a social structure that benefits the accommodation mechanisms which explain, predict, interpret, clarify and transmit culture and social practices. These mechanisms give shape to the classroom—a space for teacher-student interactions. As a result, the symbolic focus of education offers an opportunity for conducting research which values cultural diversity, the student’s learning context, the stimulus given to individual intelligences and the changing human interactions. In this way, a more altruistic solution to problems is provided.